2015
DOI: 10.1159/000373970
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 Displays a Protective Role Against Cardiomyocyte Hypertrophy by Targeting Cardiac Troponin I-Interacting Kinase

Abstract: Background/Aims: MicroRNAs play regulatory role in cardiovascular disease. MicroRNA-223 (miR-223) was found to be expressed abundantly in myocardium. TNNI3K, a novel cardiac troponin I (cTnI)-interacting and cardiac hypertrophy related kinase, is computationally predicted as a potential target of miR-223. This study was designed to investigate the cellular and molecular effects of miR-223 on cardiomyoctye hypertrophy, focusing on the role of TNNI3K. Methods: Neonatal rat cardiomyocytes (CMs) were cultured, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 28 publications
(33 reference statements)
0
43
1
Order By: Relevance
“…Lu et al reported that miR-223 was upregulated in left ventricular biopsies from patients with type 2 diabetes and that overexpressing miR-223 increased glucose uptake by upregulating Glut4 protein expression [32]. Wang et al showed that miR-223 was downregulated in ET-1 induced hypertrophic CMs and hypertrophic myocardium and that the miRNA alleviates cardiomyocyte hypertrophy by targeting TNNI3K [33]. However, Wang et al reported that miR-223 promotes cardiac hypertrophy, in which its expression is elevated [34].…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al reported that miR-223 was upregulated in left ventricular biopsies from patients with type 2 diabetes and that overexpressing miR-223 increased glucose uptake by upregulating Glut4 protein expression [32]. Wang et al showed that miR-223 was downregulated in ET-1 induced hypertrophic CMs and hypertrophic myocardium and that the miRNA alleviates cardiomyocyte hypertrophy by targeting TNNI3K [33]. However, Wang et al reported that miR-223 promotes cardiac hypertrophy, in which its expression is elevated [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although ET-1 and PE have been thought to induce ventricular hypertrophy [1, 5, 9-12, 46], signal transduction pathways for their activation of transcriptional regulators were poorly understood. Our study provide new evidence that the transcription factor CREB is activated mainly via IPR2-mediated Ca 2+ release and subsequent PKC/PKD-CaMKII signaling in ventricular myocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an in vitro work by Wang et al (43) observed that the expression of miR-223 was decreased in endothelin-1-triggered hypertrophic neonatal cardiomyocytes and hypertrophic hearts. Transfection of neonatal cardiomyocytes with mimic miR-223 attenuated endothelin-1-induced cell hypertrophy by directly down-regulation of TNNI3K (cardiac troponin I-interacting kinase) (43). However, TNNI3K was reported to improve cardiac function and promote physiological hypertrophy without increase in interstitial fibrosis (44).…”
Section: Volume 291 • Number 30 • July 22 2016mentioning
confidence: 99%